2018
DOI: 10.1101/lm.047001.117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of drugs of abuse on executive function: characterizing long-term changes in neural correlates following chronic drug exposure and withdrawal in rats

Abstract: Addiction has long been characterized by diminished executive function, control, and impulsivity management. In particular, these deficits often manifest themselves as impairments in reversal learning, delay discounting, and response inhibition. Understanding the neurobiological substrates of these behavioral deficits is of paramount importance to our understanding of addiction. Within the cycle of addiction, periods during and after withdrawal represent a particularly difficult point of intervention in that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 168 publications
(245 reference statements)
6
20
0
Order By: Relevance
“…Altogether, these results replicate previous findings that rats demonstrate a preference for higher-valued rewards through their choices and reaction times, and that responding is biased towards high-valued rewards in animals previously exposed to cocaine (Brockett et al, 2018; Burton et al, 2018b, 2017; Vázquez et al, 2019). Interestingly, in contrast to previous studies, we found that cocaine-exposed rats were overall more accurate on forced-choice trials ( Fig .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Altogether, these results replicate previous findings that rats demonstrate a preference for higher-valued rewards through their choices and reaction times, and that responding is biased towards high-valued rewards in animals previously exposed to cocaine (Brockett et al, 2018; Burton et al, 2018b, 2017; Vázquez et al, 2019). Interestingly, in contrast to previous studies, we found that cocaine-exposed rats were overall more accurate on forced-choice trials ( Fig .…”
Section: Resultssupporting
confidence: 89%
“…Notably, we have not observed these context signals in any other brain area that we have recorded from in rats performing this task (Brockett et al, 2018; Bryden et al, 2011; Burton et al, 2018b, 2017, 2015,2014b, 2014a; Kashtelyan et al, 2012; Roesch et al, 2007, 2006, 2012; Roesch and Bryden, 2011; Takahashi et al, 2017; Vázquez et al, 2019). Thus, context-related signals related to delay and size blocks appear to be unique to insula.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Cocaine disrupts NAc's ability to encode reward predictions and expectancies during delays preceding reward delivery [23]. It also impairs signed prediction error signals generated by VTA-DA neurons, and alters encoding in DLS, in line with elevated response biases on free-choice trials [23,58]. We suspect that artificially stimulating ACC in cocaine-exposed rats will repair many of these problems, via mechanisms that focus neural resources to task events following expectancy violationsleading to better prediction and error encoding in both NAc and VTA-DA neurons, and stronger cognitive control over DLS.…”
Section: Discussionmentioning
confidence: 99%